Evaluation of the Effect of Implant Localization on the Anterior Maxilla - Bolukbasi, Nilufer; Kocal, Ali; Ozdemir, Tayfun (ISTANBUL UNIV PRESS, ISTANBUL UNIV RECTORATE, 2012)
Purpose: The puipose of this study was to analyze the effects of dental implant locations on strain values in the anterior maxilla by finite element analysis. Material and Methods: Computed tomography was used to derive the geometry of maxillary five models with different implants locations. The configurations of implants in these models were as follows; two canines in first model, two canines and one central incisor in second model, two canines and two central incisors in third model, two canines and one lateral incisor in fourth model and two canines and two lateral incisors in fifth model. Results: A load of 100 Newton was applied to each crown in vertical loading and 100 Newton was applied to canine sites in horizontal loading. Highest strain values were calculated on the crestal bone. The fifth model was found the most risky model in vertical loading and least risky model in horizontal loading. Conclusion: The results of this study may support to the treatment planning for anterior maxilla At risky sites, bone-implant contact area may be increased to reduce the resorption.
Keywords: Dental implant; anterior maxilla; occlusal load; strain; finite element analysis; Dentistry, Oral Surgery & Medicine